Multimodel projections and uncertainties of irrigation water demand under climate change. Issue 17 (10th September 2013) - Wada, Yoshihide; Wisser, Dominik; Eisner, Stephanie; Flörke, Martina; Gerten, Dieter; Haddeland, Ingjerd; Hanasaki, Naota; Masaki, Yoshimitsu; Portmann, Felix T.; Stacke, Tobias; Tessler, Zachary; Schewe, Jacob
Abstract [1] Crop irrigation is responsible for 70% of humanity's water demand. Since the late 1990s, the expansion of irrigated areas has been tapering off, and this trend is expected to continue in the future. Future irrigation water demand (IWD) is, however, subject to large uncertainties due to anticipated climate change. Here, we use a set of seven global hydrological models (GHMs) to quantify the impact of projected global climate change on IWD on currently irrigated areas by the end of this century, and to assess the resulting uncertainties arising from both the GHMs and climate projections. The resulting ensemble projections generally show an increasing trend in future IWD, but the increase varies substantially depending on the degree of global warming and associated regional precipitation changes. Under the highest greenhouse gas emission scenario (RCP8.5), IWD will considerably increase during the summer in the Northern Hemisphere (>20% by 2100), and the present peak IWD is projected to shift one month or more over regions where ≥80% of the global irrigated areas exist and 4 billion people currently live. Uncertainties arising from GHMs and global climate models (GCMs) are large, with GHM uncertainty dominating throughout the century and with GCM uncertainty substantially increasing from the midcentury, indicating the choice of GHM outweighing by far the uncertainty arising from the choice of GCM and associated emission scenario.